Influencia de la enfermedad periodontal en el control metabólico de pacientes con diabetes mellitus tipo 2: revisión de la literatura - Steffens, Joao Paulo; Glaci Reinke, Stella Maria; Munoz, Miguel Angel; dos Santos, Fabio Andre; Pilatti, Gibson Luiz (Soc Médica Santiago, 2010)
There may be an interaction between periodontal disease and sonic systemic diseases such as diabetes mellitus The objective of this review was to verify by means of a review of clinical trials if is a positive association between periodontal disease and the glycerine control of type 2 diabetes mellitus (DM 2) patients Eleven articles that fit the study criteria were revised It was concluded that periodontal disease may influence the metabolic control of 2 Additional studies with larger sample sizes and longer follow up are necessary for a better clarification of this issue (Rev Med Chile 2010 138 1172 1178)
Review on periodontal disease and metabolic control of diabetes mellitus
Keywords: Blood glucose; Diabetes Mellitus; Type 2 Periodontal diseases